Educational Psychology: An Imperative Tool for Effective Management of Resources in Educational Institutions (Journal of Guidance and Counselling Studies, 2024)
This paper discussed educational psychology as an imperative tool for effective management of resources in educational institutions. The rationale for this is that the lack of knowledge of educational psychology by school managers is a principle reasons for the difficulties experienced in management of resources in educational institutions. This does not go well for the education system of the country. The paper highlighted the concept of educational psychology, concept of educational management, management of educational resources, provision and management of resources in education, challenges of effective management of resources in educational system, relevance of educational psychology for effective management of resources in education. This will enhance better service delivery of school managers for the attainment of the goals and objectives for which educational institution are established.
Keywords: Education; Educational Psychology; Education Management; Management of Resources; Resources